Resilience, adaptation and expected support for food security among the Malaysian east coast poor households - Alam, Md Mahmudul; Wahid, Abu N.M.; Siwar, Chamhuri (Emerald Publishing Limited, 2018)
Purpose – Sustainable food security at the household level is one of the emerging issues for all nations. It is expected that the patterns of household resilience factors and adaptation practices have a strong linkage with household food security. The purpose of this paper is to seek an effective technique of adaptation for food security and the required types of support for adaptation to food insecurity among the poor and low-income households in Malaysia. Design/methodology/approach – This study was based on primary data that were collected in July-October 2012 through a questionnaire survey among 460 poor and low-income households from the Pahang, Kelantan, and Terengganu states of Malaysia. The samples were selected from E-Kasih poor household database based on a two-stage cluster random sampling technique. The study considered household food security as household food availability and food accessibility, and ran ordinal regressions to find out the linkages of household food security with household resilience factors, adaptation practices, and expected support for adaptation to food security. Findings – The study concludes that several resilience factors and adaptation practices were statistically significant to household food security, and several external supports were statistically and significantly needed to ensure household food security. Therefore, to ensure sustainable household food security in Malaysia, the food security programs need to be integrated with sustainable development goals (SDGs) and climatic changes adaptation programs, and the involvement of relevant stakeholders are crucial. Originality/value – This study is a pioneer work based on primary data that empirically measured the linkages of household food security with household resilience factors, adaptation practices, and expected support for adaptation to food security in Malaysia. This study also discussed some issues related to the climate change linkage, which would help future climate change research. The findings of the study will be beneficial for all the stakeholders, including policy makers related to the food security and climate change adaptation.